Competition and Coalition among Underwriters: The Decision to Join a Syndicate - SONG, WEI‐LING (Journal of Finance, 2004)
ABSTRACT This paper studies the decision of lead investment banks to organize hybrid syndicates (commercial banks participating as co‐managers) versus pure investment bank syndicates. The findings show that hybrid underwriting issues are more challenging to float. Compared to pure investment bank syndicates, hybrid syndicates serve clients that are smaller, have lower common stock rankings and less prior access to the capital markets, rely more on bank loans, and invest less capital but issue larger amounts, which indicates that commercial banks' participation enhances hybrid services. Moreover, lead investment banks tend to invite banks' participation when clients exhibit higher loyalty in reusing their services.